Assessment of wind-to-hydrogen (Wind-H2) generation prospects in the Sultanate of Oman - Ahshan, Razzaqul; Onen, Ahmet; Al-Badi, Abdullah H. (Renewable energy, 2022)
Economic feasibility is one of the essential factors for choosing a project to launch. Hence, this study focused on assessing the economic viability of hydrogen generation using wind energy in the Sultanate of Oman. On this subject, wind energy potential for the selected sites was first investigated. Followed by Levelized Cost of Energy (LCOE), hydrogen production, the energy efficiency of hydrogen generation, and the Levelized Cost of Hydrogen (LCOH) production were examined. Two key factors, wind turbine power curve adjustment and turbine performance degradation during the project lifetime, were incorporated in the wind energy assessment, hydrogen production, and their costs for a site. This study has considered 18 locations throughout the country to evaluate hydrogen generation and the cost. The LCOE was found to be 0.0349–0.0701 USD/kWh without degradation and 0.0398–0.0801 USD/kWh with degradation. It also discovered the rank of the potential sites based on the merit order of hydrogen production. It showed that Masirah and Thumrait were the most suitable sites, whereas Sur was the least qualified. The LCOH for the most appropriate place, Masirah, is 3.37 USD/kg. The LCOH in Sur, a least suitable site, was found to be 6.15 USD/kg. Finally, a sensitivity analysis was done to identify the factors that significantly alter green hydrogen production costs in Omani conditions. The outcomes reveal that Wind-H2 production has significant potential with a cost-effective levelized cost in the Sultanate of Oman. •Investigating wind-powered green hydrogen production potential for Oman.•Economic analysis for glaring levelized cost of wind-powered electricity and LCOH.•LCOH is equal to 3.37–6.13 USD/kg for various locations in Oman.•Assessment includes air density and WT power curve corrections, and carbon price.•Electricity and electrolyser capital costs are most influential variables for LCOH.